THE USE OF POWTOON IN IMPROVING STUDENTS’ ENGLISH SKILLS - Ni Made Yuli Parwati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The aim of this study is to explain the use of PowToon in improving students’ English skills. The technology has grown and impacted the learning including the learning media. It left the reverse in the way teacher delivers the material. Library research method was utilized to collect the data. The instruments of this research were journals, e-books, and library findings. The finding revealed that PowToon could enhance students’ English skills. It also has a lot of benefits such as colorful fonts, moving animation, combination of visual and auditory, text and music that could help students in improving their English skills.